Fashion entrepreneurship : the creation of the global fashion business - Karra, Neri (Routledge, 2022)
"Fashion generates over a trillion dollars in sales annually and has the priceless ability to beguile its customers around the world. Fashion Entrepreneurship: The Creation of the Global Fashion Business provides the first authoritative history of the global fashion industry, from its emergence to the present day, with a focus on the entrepreneurs at the nucleus of many of the world's influential brands. It shows how successive generations of entrepreneurs built and developed the brands, democratising access to fashion brands throughout the world. This book analyses the careers of the greatest fashion entrepreneurs from the 19th century onward, including such legendary names as Charles Worth, Coco Chanel, Christian Dior, Yves Saint Laurent and Giorgio Armani. It shows how this distinct form of entrepreneurship has arisen and what lessons new entrepreneurs can learn from the past to create thriving fashion businesses in today's rapidly changing modern world. Filled with fascinating stories from the world of fashion, as well as detailed business analysis and practical advice for people looking to create successful brands, Fashion Entrepreneurship is an essential read for students of fashion and entrepreneurship, and anyone looking to understand, and succeed in, this most glamorous of industries"- Resumé vydavatele
Keywords: oděvnictví -- dějiny; módní průmysl -- dějiny; módní návrháři -- dějiny; clothing trade -- history; fashion industry -- history; fashion designers -- history; elektronické knihy; monografie; electronic books; monographs